Pemanfaatan Serbuk Gergaji Kayu Sengon (Albizia falcataria) dan Kotoran Kambing Sebagai Bahan Baku Pupuk Organik Cair dengan Penambahan Effective microorganism-4 (EM4) - Ansori, Ahmad; , Dra. Aminah Asngad, M.Si (2017)
Liquid organic fertilizer is a solution from the decomposition of organic materials. Sawdust falcata and goat manure can be combined as a liquid organic fertilizer basic materials. EM4 is used as a bio-activator in this study. The aim of research to determine the content of macronutrients (N, P, and K) liquid organic fertilizer made from sawdust falcata (Albizia falcataria) and goat manure with the addition of Effective micoorganism-4 (EM4). This study uses a completely randomized design (RAL) with two factors, namely 1 ratio material (P) sawdust sengon : a mixture of goat manure and fruit waste (P1 = 50% : 50%, P2 = 60% : 40%, P3 = 75% : 25%) and factor 2 concentrations of Effective microorganism-4 (S) (S1 = 5%, and S2 = 15%). The results of research shows the highest N content in treatment P3S1 is 0.14% and the lowest in treatment P2S2 is 0.09%. The highest P content in treatment P1S2 is 692.11 ppm and the lowest in treatment P3S1 is 256.01. The highest K content in treatment P1S2 is 0.24% and the lowest in treatment P3S1 is 0.13%